Waste minimization in selected food industries in Region VI - Gubuan, Leonor Felisa T. (1998.)
Five food industries in Region VI were chosen as subjects / respondents in a survey to establish the importances of waste minimization strategies in their overall waste management program.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Waste; Waste management; Food industries